(untitled) (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: To study the drug release profiles obtained by auto-dilution and auto-mixing of dissolution aliquots of naproxen sodium tablets IP and evaluate it statistically. Materials and Methods: Naproxen sodium active pharmaceutical ingredient was procured from Divis Laboratory (India). The drug dissolution media was prepared by diluting media concentrates (Jawa buffer concentrate pH 7.4, Electropharma) to obtain phosphate buffer pH 7.4. Investigations are necessary to understand the effect of dilution and mixing efficiency on the ultra-violet (UV) analysis of in-vitro dissolution aliquots of high dose drugs. In the present research, two independent sets of studies were carried out for the determination of the percentage of drug released from high-dose naproxen sodium tablets. Results and Discussion: Dissolution studies and subsequent drug analysis for high-dose oral solid dosage form is a challenge to a drug analyst. Automation in dilution and mixing of collected sample can offer a measure toward streamlining the dilution and mixing procedure resulting in uniformity of drug dissolution profile. Experimental data from manual as well as automated methods of sampling, dilution and mixing were obtained and evaluated statistically for variations in data point values. The similarity and difference factors were found to be 93.05 (f2) and 1.10 (f1), respectively. Both the methods of dissolution aliquot mixing were compared by applying the two-tailed paired Studentâ€™s t-test. Studentâ€™s â€œtâ€ statistics showed that there was non-significant difference between the two methods (P â‰¥ 0.05). Conclusion: The analysis of the data ensured a statistical closeness of the results obtained and empowered use of an automated dissolution system capable of diluting and effectively mixing dissolution aliquots before UV spectrophotometric analysis